2019
DOI: 10.1186/s13058-019-1191-3
|View full text |Cite
|
Sign up to set email alerts
|

A functional role for the cancer disparity-linked genes, CRYβB2 and CRYβB2P1, in the promotion of breast cancer

Abstract: Background In the USA, the breast cancer mortality rate is 41% higher for African-American women than non-Hispanic White women. While numerous gene expression studies have classified biological features that vary by race and may contribute to poorer outcomes, few studies have experimentally tested these associations. CRYβB2 gene expression has drawn particular interest because of its association with overall survival and African-American ethnicity in multiple cancers. Several reports indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…In addition to CYP4Z2P, some pseudogene-derived lncRNAs were also found to function as oncogenes in breast cancer. For example, Liu et al (2017a) confirmed that SUMO1P3 promoted proliferation, migration and invasion of breast cancer; Barrow et al (2019) found that CRYbetaB2P1 was upregulated in breast cancer and facilitated progression of breast cancer by increasing CRYbetaB2 expression; demonstrated that FTH1P3 led to paclitaxel resistance of breast cancer. PTTG3P was markedly upregulated in breast cancer samples compared with normal controls and its upregulated linked to poor prognosis of patients with breast cancer .…”
Section: Breast Cancermentioning
confidence: 99%
“…In addition to CYP4Z2P, some pseudogene-derived lncRNAs were also found to function as oncogenes in breast cancer. For example, Liu et al (2017a) confirmed that SUMO1P3 promoted proliferation, migration and invasion of breast cancer; Barrow et al (2019) found that CRYbetaB2P1 was upregulated in breast cancer and facilitated progression of breast cancer by increasing CRYbetaB2 expression; demonstrated that FTH1P3 led to paclitaxel resistance of breast cancer. PTTG3P was markedly upregulated in breast cancer samples compared with normal controls and its upregulated linked to poor prognosis of patients with breast cancer .…”
Section: Breast Cancermentioning
confidence: 99%
“…Genetics of human populations contribute to the propensity and severity of diseases 37,39,41,41,45,[60][61][62][63][64][65] . Sometimes the contribution is straightforward; a single allele variation found in Ashkenazi Jews, causes the vast majority of Tay-Sachs disease 66 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, obtaining adequate sample sizes for statistical analysis of populations is very important but difficult or expensive to address. Ethnic bias and practical factors (such as subject availability) often result in insufficient numbers of subjects from many populations to be represented in medical studies; this lack of representation prevents the development of precise prognosis or therapy based on genetics 39,97 . Similarly, diverse socioeconomic contexts may not be well represented among the individuals sampled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations